Experiment and Numerical Simulation of Seawater Intrusion under the Influences of Tidal Fluctuation and Groundwater Exploitation in Coastal Multilayered Aquifers - Qiaona Guo; Jiangwei Huang; Zhifang Zhou; Jinguo Wang (Geofluids)
The dynamic behavior of groundwater flow and salt transport is affected by tide and pumping in coastal multilayered aquifers. In this paper, two groups of experiments were conducted considering different constant head inland boundaries. The fluctuation of the groundwater level and the process of seawater intrusion in the multilayered aquifers were observed. A two-dimensional SEAWAT model is developed to simulate the seawater intrusion to coastal aquifers under the influences of tidal fluctuation and groundwater exploitation. The hydrogeological parameters in the model are calibrated by the records of the groundwater level and salinity measurements. The results showed that the simulated groundwater level and salt concentration match the observation well. The groundwater level has the characteristics of periodic fluctuation with tide. The lag time of the groundwater level fluctuation in each monitoring point increases slightly with the increasing distance from the saltwater chamber. For the low tide, the inland freshwater recharge has main effect on groundwater level fluctuation. The rising tide has a negative effect on the drawdown of the groundwater level induced by pumping. For the high tide, the tide plays a major role on groundwater level fluctuation, compared with the inland freshwater recharge. Compared with the condition of high head of inland recharge, larger saltwater intrusion lengths and area have been observed and simulated in the aquifer, which means that faster inland motion of the seawater wedge would occur when the inland recharge is small in the coastal aquifers. It revealed that inland recharge plays a major role in the seawater intrusion for the same pumping rate of groundwater in different seasons. The analysis provides insights into how the tide fluctuation, groundwater pumping, and inland recharge effect on the area and rates of seawater intrusion.